Knowledge of Emergency Management of Traumatized Teeth among Schoolteachers in Mashhad, Iran - Maryam Mehrabkhani; Behjatolmolok Ajami; Iman Parisay; Ali Bolboli; Golsa Akbarian (Journal of Dental Research, Dental Clinics, Dental Prospects, 2015)
Background and aims. Dental trauma is an important oral health problem in children that requires immediate and appro-priate management for long term success. The aim of this study was to evaluate the knowledge of elementary school teach-ers about emergency management of traumatic dental injuries in children. Materials and methods. A total of 163 teachers from 21 elementary schools from Mashhad, Iran participated in this study. Data were collected using a two-part questionnaire comprised of questions regarding demographic data and partici-pants' knowledge about dental trauma. Results. The level of the teachers' knowledge was moderate (53.3%). Of the 163 participants, 104 (63.8%) were females and 59 (36.2%) were males. Among several predictors that were surveyed in this study, only the age of respondents signifi-cantly impacted the teachers' knowledge (P = 0.004). Conclusion. The results of this study showed the moderate level of knowledge of teachers regarding emergency manage-ment of traumatized teeth. Adding dental trauma management courses in the teacher training curriculum and requiring teachers to be updated in regards to this issue can improve their knowledge and thus led to better management of traumatic dental injuries in children.